2022
DOI: 10.12688/f1000research.122115.1
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-negative staphylococci as an evolving mastitis causing organism in cows: A review

Abstract: The present review attempts to address the emergence of a fast-growing mastitis causing pathogen – coagulase-negative staphylococci (CNS) – and its multi-facet roles in dairy farms. CNS is divided into numerous species, but only a few succeed in bovine mastitis. The two predominant CNS species causing mastitis are Staphylococcus chromogenes and Staphylococcus simulans. These two mostly known CNS affects dairy cows at varied parities and at different lactation stages. CNS have been judged to be the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Mastitis is caused by a plethora of pathogens, including Staphylococcus chromogenes (SC). Staphylococcus chromogenes is one of the most predominant species of coagulase-negative staphylococci (CNS) and is considered an emerging mastitis pathogen of dairy cows in many countries [ 1 , 2 ]. It is also the most predominant CNS on Canadian dairy farms [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis is caused by a plethora of pathogens, including Staphylococcus chromogenes (SC). Staphylococcus chromogenes is one of the most predominant species of coagulase-negative staphylococci (CNS) and is considered an emerging mastitis pathogen of dairy cows in many countries [ 1 , 2 ]. It is also the most predominant CNS on Canadian dairy farms [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain NASM strains (e.g. S. chromogenes ) have demonstrated the ability to suppress major mastitis-causing bacteria through the secretion of antimicrobial peptides, specifically bacteriocin [ 7 , 44 ]. Bacterial activation prompts neutrophils to release antimicrobial peptides for mastitis-causing bacteria elimination.…”
Section: Discussionmentioning
confidence: 99%
“…They have been isolated from various cows’ anatomical sites and the dairy environment [ 2 , 4 , 5 ]. Although previously considered insignificant pathogens, NASM, for example, S. chromogenes, S. epidermidis , S. simulans , S. xylosus , S. haemolyticus , and Mammaliicoccus fleurettii , may pose a severe threat to the health of bovine udders [ 2 , 3 , 6 , 7 ]. NASM can potentially cause persistent IMIs [ 8–10 ], resulting in increased somatic cell count (SCC) and reduced milk production [ 6 , 7 , 10 ]; however, the impact of NASM on udder health is still a topic of discussion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the cows recorded with less than 150,000 cells/ml milk before and after FAI were designed uninfected (category 1 control). This cut-off point is important because IMI with skin flora opportunists as CNS, have been found that induce light SCC levels in the milk of affected cows [4] [16] [17].…”
Section: Discussionmentioning
confidence: 99%